Use of cryopreserved, ultra-thick amniotic membrane allograft for colorectal and intestinal anastomoses - John Charles Blaney (International Journal of Gastrointestinal Intervention, 2024)
Background: Anastomotic leak (AL) is one of the most feared complications following intestinal surgery and is associated with increased complications, costs, length of hospital stay, and mortality. While many pre-clinical animal model studies have successfully demonstrated the efficacy of amniotic membrane (AM) in preventing AL, its clinical utility is less reported. Methods: A single-center, retrospective study was performed on patients who underwent intestinal surgery followed by end-to-end or side-by-side single layer anastomosis and placement of cryopreserved, ultra-thick AM. Post-operative outcomes were assessed including time to first defecation, length of hospital stay, and complications, including incidence of AL. Results: Eleven consecutive patients (7 male, 4 female) underwent open (n = 2) or laparoscopic (n = 9) resection of the sigmoid (n = 6), cecum (n = 2), ascending colon (n = 1), rectum (n = 1), and small bowel (n = 1). Surgery was uneventful in all cases. The time to first defecation was 3.5 ± 2.1 days. After an average follow up of 65.3 ± 42.0 days, none of the patients suffered an AL nor required another colorectal procedure. Conclusion: These preliminary findings suggest the use of cryopreserved, ultra-thick AM following intestinal surgery is safe and may be beneficial in reducing the incidence of AL and post-operative complications. Larger prospective, randomized trials are warranted.